2020
DOI: 10.1186/s12903-020-01197-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral health conditions in children with idiopathic nephrotic syndrome: a cross-sectional study

Abstract: Background: Nephrotic syndrome is one of the chronic illnesses in the pediatric age group. The aim of this study was to assess the oral health of patients with steroid-sensitive idiopathic nephrotic syndrome (iNS). Methods: A case-control study was performed on iNS patients and healthy from May 2018 to April 2019. Dental caries was assessed by the World Health Organization criteria, developmental defects of enamel by the mDDE index, oral hygiene by the OHI-S and API, and gingival condition by the GI. Oral heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The examinations were performed from May 2018 to April 2019. The detailed data on oral health parameters and questionnaire items were published earlier [ 16 ]. In this paper, we used only several basic oral health parameters, which could potentially influence the studied salivary components.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The examinations were performed from May 2018 to April 2019. The detailed data on oral health parameters and questionnaire items were published earlier [ 16 ]. In this paper, we used only several basic oral health parameters, which could potentially influence the studied salivary components.…”
Section: Methodsmentioning
confidence: 99%
“…Data on gender, age, frequency of toothbrushing, use of fluoridated toothpaste and topical professional application of fluoride specimens, and diet were reported by the parents of the participants. The detailed questionnaire items were published earlier [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral hygiene practice among children with PNS has been reported as poorer than among healthy controls [10], with significantly increased food debris and dental plaque [8,11]. Despite not providing specific calculus indices, two studies by Babu and Jana (2014) [12] and Subramaniam (2012) [8] revealed a high incidence of calculus, especially at the lingual surface of mandibular incisors, in children with PNS.…”
Section: Introductionmentioning
confidence: 99%
“…Routine hospitalization and a particular diet impede oral health care [13]. Evidence shows that poor oral care, high snack consumption, and the lack of parental supervision contribute to the worsening of oral health of children with PNS [10,12].…”
Section: Introductionmentioning
confidence: 99%